3D mapping of sublevel caving (SLC) blast rings and ore flow disturbances in the LKAB Kiruna mine - Wimmer, Matthias; Nordqvist, Anders A.; Ouchterlony, Finn; Selldén, Håkan; Lenz, Gunther (Luleå tekniska universitet, Geoteknologi, 2012)
Sublevel caving (SLC) is a highly productive mining method with the major disadvantages of irrepressible ore loss and dilution. The confined blasting situation of SLC rings is commonly regarded to have a significant impact upon the material flow characteristics and hence on the overall performance. The initial conditions for the ore flow after blasting are unknown, as both the blasted geometry and the fragmentation itself are normally hidden. However, when opening a new drawpoint and in hang-up situations an inspection of the actual conditions is feasible. For this purpose, a remotely operated 3D photogrammetry system was custom built and used to reconstruct the ring front and/or cavity as a geo-referenced mesh model with colour information. Various blasting situations have been observed and this allowed a deeper study of the i) broken geometry and height, ii) over- and underbreak and their effects on subsequently blasted rings, iii) interaction effects between adjacent holes/rings, iv) drilling accuracy based on identified boreholes and v) mapping of geological structures and their influence on the blast result. The capabilities of the 3D image acquisition system to evaluate the blasting results are demonstrated with an example, in which a series of blasts were surveyed. Monitoring under hang-up situations, has then revealed the actual effects from confined blasting and gravity flow related issues. The 3D photogrammetry system is now increasingly being used to study hang-ups. By revealing and quantifying hitherto inaccessible information, the system has proven to be a valuable tool in increasing the understanding of both SLC breakage and flow. Godkänd; 2012; Bibliografisk uppgift: CD-ROM; 20121112 (matwim)